Digital Transformation Strategies of Islamic Banks to Enhance Financial Inclusion: A Literature Review - Fakhri Ahmad Zainunnuri; Sri Dewi Miladiyah; R. Ilfan Muhammad Abdurrasyid; Amin Basir; Popon Srisusilawati (Talaa : Journal of Islamic Finance, 2026)
This study examines the challenge of low Islamic financial inclusion in Indonesia despite the growth of digital financial services and Islamic financial literacy. Although digitalization has expanded access to financial services, Islamic banks still face difficulties in translating technological advancement into broader and sustainable Sharia-compliant inclusion. This condition highlights the need for an integrated digital transformation strategy that aligns organizational capabilities with user acceptance within the Islamic finance framework. Using a qualitative literature review of academic studies and institutional reports, this study analyzes digitalization strategies in Islamic banking. The findings show that Islamic banking applications, collaboration with halal fintech, strengthened technological infrastructure, and maqashid sharia-based product innovation increase the adoption of Islamic financial services. Theoretically, this study integrates the Technology Acceptance Model and Dynamic Capabilities Theory to explain how organizational readiness and user perceptions jointly support digital transformation. The study confirms that digitalization can accelerate Islamic financial inclusion when aligned with Sharia-based values.